Substitute with the value of n in the equation to get m as follows:
at n=1:
2m=-6(1)-5=-6-5=-11
m = -11/2
at n=2:
2m=-6(2)-5=-12-5=-17
m = -17/2
at n=3:
2m=-6(3)-5=-18-5=-23
m = -23/2
The system of inequalities which is represented in the graph shown (see attachment) is:
- y ≥ x² -2x -3
- y ≤ x +3
<h3>What is an inequality?</h3>
An inequality can be defined as a mathematical relation that compares two (2) or more integers and variables in an equation based on any of the following:
- Less than or equal to (≤).
- Greater than or equal to (≥).
<h3>What is a graph?</h3>
A graph can be defined as a type of chart that's commonly used to graphically represent data on both the horizontal and vertical lines of a cartesian coordinate, which are the x-axis and y-axis.
By critically observing the graph which models the system of inequalities shown, we can infer and logically deduce the following points:
- Both boundary lines on the cartesian coordinate are solid. Thus, the inequalities will both have the "equal to" sign.
- The shading occurred above the quadratic boundary line. Thus, the inequalities below the linear boundary line is given by y ≥ x² + and y ≤ x +
In conclusion, we can infer and logically deduce that the system of inequalities which is represented in the graph shown (see attachment) is:
- y ≥ x² -2x -3
- y ≤ x +3
Read more on graphs here: brainly.com/question/25875680
#SPJ1
Change in April's weight is -7
<em><u>Solution:</u></em>
Let the initial weight be "x"
April lost 5 pounds in her first week of college
First week = lost 5 pounds
Therefore, x - 5
Over the next three weeks she lost 3 pounds, gained 2 pounds, and then lost 1 pound
<em><u>Next three week:</u></em>
Lost 3 pound
Gained 2 pound
Lost 1 pound
<em><u>Therefore, weight after 4 weeks is given as:</u></em>
x - 5 - 3 + 2 - 1 = x -7
After 4 week, the weight is x - 7
<em><u>The change in April weight is given as:</u></em>
Weight after 4 week - initial weight = x - 7 - x = -7
Thus change in April's weight is -7 (Negative sign represents loss in weight )
<span><u><em>Answer:</em></u>
(5 * 1) + (9 * 0.1).<span>
<u><em>Explanation:</em></u>
To write a number in expanded form you have each digit multiplied by its numbers place and add each digit together. 5 is in the ones place so it becomes (5 * 1).
9 is in the tenths place so it becomes (9 * 0.1).
add them together to get (5 * 1) + (9 * 0.1)</span></span>
First your going to use commutative property to reorder the terms , so it would be
5x^4-x-35x^3+7 , then your going to factor out x & -7 from the equation once you factor that out you should have x(5x^3-1)-7(5x^3-1) after you got that your going to factor out 5x^3-2 and get the answer (x-7)(5x^3-1) which is your final answer.